Recent economic development and outlook in industrial countries - Adolf Ahnefeld; Dietmar Gebert; Jürgen Roth; Joachim Scheide; Norbert Walter (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1977)
The upswing in Europe, North America and Japan since mid-1975 has been unsteady. It has been sufficiently modest to allow a — however slight — decline of inflation rates. Since economic policy refrained from massive reflation, the shortrun outlook remains for a moderate recovery with no rekindling of inflation. High unemployment and weak investment can partly be attributed to the abrupt change to a restrictive course in 1973/1974 which led to unintended increases of real wages and to a dramatic profit squeeze. Moreover, there have been increasing changes in the structure of demand and production techniques as well as political uncertainties which have prevented a marked improvement of the investment climate. This diagnosis calls for a steady economic policy, less aggressive wage policy, and incentives to promote innovative spirit and risk taking. Although money illusion and exchange rate illusion have largely vanished and reduced the effectiveness of short-term stimulation measures, most countries are far from pursuing a steady and pre-announced course. In strong countries — the United States, West Germany and Japan — the reduction of the share of public absorption especially through a shortfall of public investment since 1974 was a retarding factor for improving employment and growth. In weak countries — for example the United Kingdom and Italy — an easy money policy continued to produce high inflation rates and increasing external imbalances. Only after drastic exchange rate depreciations in 1976 did these countries — sometimes too drastically — turn to a restrictive policy course. Cooperation in matters of economic policy, often misunderstood as the sharing of evils, should be designed as help for self-help. International credits should be granted under the condition that the recipient country pursues a stability-oriented policy and refrains from restricting trade.
Keywords: 330